What Can Boost Female Labor Force Participation in Asia? - Kinoshita, Yuko (IMF Working Papers; Working Paper ;, 2015)
Both Japan and Korea are trying to boost female labor force participation (FLFP) as they face the challenges of a rapidly aging population. Though FLFP has generally been on a rising trend, the female labor force in both countries is skewed towards non-regular employment despite women's high education levels. This paper empirically examines what helps Japan and Korea to increase FLFP by type (i.e., regular vs. non-regular employment), using the SVAR model. In so doing, we compare these two Asian countries with two Nordic countries Norway and Finland. The main findings are: (i) child cash allowances tend to reduce the proportion of regular female employment in Japan and Korea, (ii) the persistent gender wage gap encourages more non-regular employment, (iii) a greater proportion of regular female employment is associated with higher fertility, and (iv) there is a need for more public spending on childcare for age 6-11 in Japan and Korea to help women continue to work.